Interrelações existentes entre os escoamentos de ventos e os padrões de ocupação do solo nos bairros do Cabo Branco e Tambaú/João pessoa - PB - Peregrino, Paulo Sergio Araújo (2005)
This research aimed to evaluate how four patterns of the urban use and occupation are interrelated in the wind flow comportment, relating to different settings which were considered in: the actual occupation pattern of the areas of Cabo Branco and Tambaú in Joao Pessoa, the capital city of Paraíba State, in the same area, where the three other types were suggested and carried out, the first one relating to the actual legislation considering heavy urban density and the second other two have investigated the possibility of vertical structure for such density. By applying reduced scale modeling experiments in aerodynamic tunnels and by using the erosion figure technique (of sand) (JANEIRO and SARAIVA, 1980), with the methodology developed by Silva (1999), analysis have reached the conclusion that the legal standard induced by the actual legislation may giving permission for irreversible loss in the urban improvement and environmental quality associated to buildings around the beach areas of the whole city in the near future.